Kinetic Determination of Thiocyanate by the Reaction of Bromate with Crystal Violet Immobilized in a Polymethacrylate Matrix; Journal of Analytical Methods in Chemistry; Vol. 73, № 9 - Gavrilenko N. A. Natalia Airatovna; Saranchina N. V. Nadezhda Vasilievna; Sukhanov A. V. Aleksey Viktorovich; Fedan D. A. Dmitry Andreevich; Gavrilenko M. A. Mikhail Alekseevich (2018, 2018)
Title screen